Sarcocystis spp. em tecidos musculares de equinos do sul do Brasil destinados ao consumo humano - Cocco, Mariana (2024)
Horses are intermediate hosts of sarcocystis-forming species with worldwide distribution. This study aimed to detect the presence of Sarcocystis spp. in horse muscles destined for human consumption slaughtered in an abattoir in the state of Rio Grande do Sul, southern Brazil, using direct examination and molecular analysis. A total of 416 muscle samples from masseter and pharynx were obtained from 208 horses and examined through direct examination in order to search for cysts, which if found were submitted to DNA extractions using a Wizard Genomic DNA Purification Kit and subsequently to a nested-PCR for the 18S rRNA gene. The amplified products were subjected to Restriction Fragment Length Polymorphism (RFLP) using Dde-I and Hpa-II enzymes to differentiate Sarcocystis spp. from Sarcocystis neurona, Toxoplasma gondii and Neospora caninum. In the direct microscopic analysis were detected cysts in 15,1% (63/416) of total samples: 24,5% (51/208) from pharynx and 5,8% (12/208) from masseter. Sarcocystis spp. DNA was successfully amplified from 41,3% (26/63) of the samples subjected to molecular analysis. Detection frequencies in masseter were 41,7% (5/12) and in pharynx 41,2% (21/51). In RFLP, an enzymatic restriction pattern indicative to Sarcocystis spp. was detected in all samples tested, being 86,7% (13/15) from pharynx and 13,3% (2/15) from masseter. The identification of Sarcocystis spp. circulating in horses in the state of Rio Grande do Sul is a relevant finding, more studies are necessary to characterize S. bertrami and to identify if S. neurona is present in samples.